2014
DOI: 10.1155/2014/869572
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Expenditure Pattern of Epileptic Patients: A Study from a Tertiary Care Hospital, Kolkata, India

Abstract: Introduction. Neurological diseases are very important causes of prolonged morbidity and disability leading to profound financial loss. Epilepsy is one of the most important neurological disorders. It being a cost intensive disorder poses a significant economic burden to the country. Aims and Objectives. The study was conducted among the persons with epilepsy (PWE) to assess their expenditure pattern for epilepsy treatment and its rural urban difference. Materials and Methods. 315 PWE selected by systematic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In the current study, trend of medicine discontinuation was observed due to nonaffordability despite the fact that discontinuation of AEDs without prior consultation with the neurologist can result in serious medical consequences [ 23 ]. Rural populations face innumerable constraints including weaker financial status and having out-of-pocket expenses in epilepsy treatment [ 24 ]. The lower socioeconomic status (SES) of the patients makes them susceptible to medication nonadherence, but it can be inflamed especially during the current pandemic because of losing jobs and wages associated with a disruption in the source, which makes the provision of drugs accessible as noticed in the present study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, trend of medicine discontinuation was observed due to nonaffordability despite the fact that discontinuation of AEDs without prior consultation with the neurologist can result in serious medical consequences [ 23 ]. Rural populations face innumerable constraints including weaker financial status and having out-of-pocket expenses in epilepsy treatment [ 24 ]. The lower socioeconomic status (SES) of the patients makes them susceptible to medication nonadherence, but it can be inflamed especially during the current pandemic because of losing jobs and wages associated with a disruption in the source, which makes the provision of drugs accessible as noticed in the present study [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] Recently, Sinha and Bhaumik have estimated average direct treatment cost per month due to drugs, travel, and investigations as 219 INR (US$3.64). [ 52 ]…”
Section: Economic Impactmentioning
confidence: 99%
“…Because of epilepsy, patients lose their jobs and education along with their status in the society. Sinha & Bhaumik (2014) describe 'the children with epilepsy frequently lag in education because they find it difficult to get work. Employers wouldn't want to employ an epileptic '.…”
Section: Literature Reviewmentioning
confidence: 99%